Polyphosphate uses mTOR, pyrophosphate, and Rho GTPase components to potentiate bacterial survival in Dictyostelium - Ryan J. Rahman; Ramesh Rijal; Shiyu Jing; Te-An Chen; Issam Ismail; Richard H. Gomer (mBio, 2023)
ABSTRACT Human macrophages and the eukaryotic microbe Dictyostelium discoideum ingest bacteria by phagocytosis, and then kill the ingested bacteria. Some pathogenic bacteria secrete linear chains of phosphate residues (polyphosphate; polyP), and the polyP prevents some of the phagocytes from killing the ingested bacteria. In D. discoideum, the effect of polyP requires the G protein-coupled receptor (GPCR) GrlD, suggesting that polyP uses a signal transduction pathway to inhibit killing of ingested bacteria. Here we show that in addition to GrlD, the D. discoideum polyP signaling pathway requires the GPCR interacting arrestin-like protein AdcB, inositol hexakisphosphate kinase A (I6kA), the Rho GTPase RacE, and the target of rapamycin (TOR) component Lst8. D. discoideum also secretes polyP, and at high concentrations polyP inhibits D. discoideum cytokinesis. The polyP inhibition of bacterial killing pathway has some components that overlap and some components that are distinct from the polyP inhibition of cytokinesis pathway. These data suggest the intriguing possibility that if there is a similar polyP inhibition of bacterial killing pathway in macrophages, pharmacologically blocking this pathway could potentiate macrophage killing of pathogenic bacteria. IMPORTANCE Although most bacteria are quickly killed after phagocytosis by a eukaryotic cell, some pathogenic bacteria escape death after phagocytosis. Pathogenic Mycobacterium species secrete polyP, and the polyP is necessary for the bacteria to prevent their killing after phagocytosis. Conversely, exogenous polyP prevents the killing of ingested bacteria that are normally killed after phagocytosis by human macrophages and the eukaryotic microbe Dictyostelium discoideum. This suggests the possibility that in these cells, a signal transduction pathway is used to sense polyP and prevent killing of ingested bacteria. In this report, we identify key components of the polyP signal transduction pathway in D. discoideum. In cells lacking these components, polyP is unable to inhibit killing of ingested bacteria. The pathway components have orthologs in human cells, and an exciting possibility is that pharmacologically blocking this pathway in human macrophages would cause them to kill ingested pathogens such as Mycobacterium tuberculosis.